Pengaruh Gaya Kepemimpinan, Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan (Studi Pada Karyawan Restoran Pizza Hut Ciliwung Malang) - Ifani, Achmad Shofan; Basalamah, Muhammad Ridwan; Khalikussabir, Khalikussabir (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study aims to determine the influence of leadership style, motivation, and work discipline on employee performance. This research is a descriptive and explanatory study that explains the relationships and influences among variables through hypothesis testing. The study uses the entire population of 32 respondents from Pizza Hut Ciliwung, Malang, with online questionnaire distribution. Data analysis employs multiple linear regression using SPSS version 23. The testing results of the four hypotheses conclude that: 1. Leadership style, motivation, and work discipline together (simultaneously) have a positive and significant influence on the performance of Pizza Hut Ciliwung employees. 2. Leadership style has a positive and significant influence on the performance of Pizza Hut Ciliwung employees. 3. Employee performance at Pizza Hut Ciliwung is positively and significantly influenced by motivation. 4. Work discipline has a positive but not significant influence on the performance of Pizza Hut Ciliwung employees. Keywords: Leadership Style, Motivation, Work Discipline, Employee Performance